The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12888-018-1942-1
|View full text |Cite
|
Sign up to set email alerts
|

Is intrauterine exposure to acetaminophen associated with emotional and hyperactivity problems during childhood? Findings from the 2004 Pelotas birth cohort

Abstract: BackgroundLongitudinal studies have consistently reported that prenatal exposure to acetaminophen can to lead to an increased risk of attention deficit-hyperactivity disorder during childhood. This study aimed to investigate the association between intrauterine exposure to acetaminophen and the presence of emotional and behavioral problems at the ages of 6 and 11 years in a low-middle income country.MethodsWe performed a prospective longitudinal population-based study using data from the 2004 Pelotas birth coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 51 publications
4
41
1
Order By: Relevance
“…Tovo‐Rodrigues et al, reported sex‐specific findings in an analysis of the 2004 Pelotas Birth Cohort data. In that study, the authors found an adverse association of acetaminophen exposure with hyperactivity/inattention as well as emotional problems in boys at 6 years of age . Similar sex‐specific findings were observed by Avella‐Garcia et al, in which prenatal acetaminophen exposure was associated with a greater number of ASD symptoms in boys .…”
Section: Commentsupporting
confidence: 79%
“…Tovo‐Rodrigues et al, reported sex‐specific findings in an analysis of the 2004 Pelotas Birth Cohort data. In that study, the authors found an adverse association of acetaminophen exposure with hyperactivity/inattention as well as emotional problems in boys at 6 years of age . Similar sex‐specific findings were observed by Avella‐Garcia et al, in which prenatal acetaminophen exposure was associated with a greater number of ASD symptoms in boys .…”
Section: Commentsupporting
confidence: 79%
“…In the Brazilian 2004 Pelotas birth cohort, 6‐year‐old boys of mothers who used acetaminophen in pregnancy had higher odds of emotional (OR 1.47, 95% CI 1.07, 2.02) and hyperactivity (OR 1.42, CI 1.06, 1.92) problems, as assessed by parent‐reported SDQ scores . At age 11 years, there was a small decrease in these associations (emotional OR 1.31, CI 0.99, 1.73 and hyperactivity OR 1.25, CI 0.95, 1.65 problems).…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigators have suggested that child sex may modify associations between acetaminophen exposure and behavioural outcomes . We assessed potential effect measure modification by re‐running adjusted models stratified by sex and also computed interaction P ‐values.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations